U.S. Energy Security Achievement Policies During President Donald Trump's Term 2017-2020 - Saleh, Asst.L. Sivan Saleh Zorab; Karim, Prof.Dr. Rebwar Karim Mahmoud (Sulaimani Journal for Humanities, 2025)
The global energy system is going through a transition to a new energy system characterized by the emergence of the United States as a major exporter of oil, and the gradual shift of the shale oil revolution towards low-carbon and renewable energy sources. The shale oil revolution in the United States changed the rules of the energy game at the global level, as happened with the election of Donald Trump as President of the United States. Trump has declared his ambition to transform the United States into a global energy superpower, because it can determine the basic pillars of the global energy system. This transformation in the global energy system could be a result of the revolution that occurred in the field of shale oil on the one hand, and Donald Trump’s new economic and trade policies on the other hand.